Arang Eceng Gondok (Eichornia crassipes) sebagai Adsorben Fenol pada Limbah PLTU Palu - Tudjuka, Mora Delfita; Walanda, Daud K.; Hamzah, Baharuddin (Universitas Tadulako, 2017)
This study aims to determine the optimum capacity and weight of water hyacinth aroma to the adsorption capacity of phenol in Palu PLTU waste. The steps taken in this research are a sampling of PLTU waste, making of adsorbent, determination of phenol concentration in PLTU waste and determination of phenol concentration at equilibrium using a Spektrodirect spectrophotometer. The adsorption capacity of water hyacinth at optimum condition of phenol was determined by weight variations of 10, 20, 30, 40 and 50 mg. The resulting result after adsorption process for adsorption weight at the weight of charcoal 10 mg = 82.78%, 20 mg = 89.13%, 30 mg = 85.49%, 40 mg = 79.72% and 50 mg = 74, 42 %. The optimum weight of charcoal in phenol absorb is 20 mg with% phenol which is absorbed 89.13%. The capacity of adsorbent hailing of water hyacinth scent at optimum condition of 3.03 mg phenol/g of adsorbent.